USING TIKTOK TRENDS IN ENGLISH LANGUAGE TEACHING - Muslimova, Zh.M. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
This article explores the potential of integrating current TikTok trends into English language teaching. The pedagogical benefits of this approach are analyzed, including increased student motivation, development of communication skills, and enhanced engagement in the learning process. Special attention is given to methodological aspects of incorporating popular trends into different stages of a lesson.
Keywords: interactive learning; digital literacy; TikTok trends; communication skills; English language teaching